Innovation strategy and organisational structure: insights from an Italian family firm. (28th February 2020) - Truant, Elisa; Broccardo, Laura
The objective of this study is to verify whether an innovation strategy might offer a competitive advantage, even during periods of crisis, to a family business operating in the automotive sector. In addition, it was investigated if the company had modified its organisational structure to enhance strategy implementation. The research methodology first focused on a review of the international literature relevant to innovation in family businesses and the strategy-structure alignment. Then, a relevant Italian case study about a leader in the European vehicle-transport sector was selected and examined. In recent years, crisis has strongly affected this sector, increasing the average life of commercial vehicles. To survive and thrive over this period, in contrast with the behaviour of other companies, the family business owner adopted a proactive approach based on an innovation-focused strategy. This paper contributes to the expansion of the literature on innovation in family businesses and organisational structure.